Application of Electrohydrodynamic Method and High-Pressure Water Jets as Non-Blasting Alternative of Rock Breaking and Splitting in Open Pits - Krzysztof Kotwica (International Conference on Ground Control in Mining, 2006)
The steady demand for rock materials leads not only to on increase in mining but to the need for decreasing the loss of material in the process of exploitation as well. It brings about an increase in using of explosives in open pits and as a result an increase of after blasting gases volume, vibrations, the scattering (dispersion) of stone ect. All these factors affecting the environment lead to the research work for applying the electrohydrodynamic methods both in open casts and underground mines. In the article the authors describe the concept of this method and construction of equipment which recently have been successfully introduced in mining, the results obtained determine the possibilities of using this method and the future directions. The results of combined method with high-pressure water jets cutting and prototype equipment for separating rock blocks from the rock mass using special head with high-pressure water jets are also described.